THE CHOICE OF TYPES, LOCATIONS OF SENSORS AND CRITERIA FOR NOTIFICATION OF THE DERAILMENT OF A FREIGHT CAR ON THE BASIS OF MATHEMATICAL AND PHYSICAL MODELING - Orlova, A. M.; Lisnychyi, V. S.; Smirnov, M. V. (Science and Transport Progress, 2004)
The work considers three stages of derailment process, which are the flange climbing the railhead, the wheelset falling down from the rail and the wheelset motion over the sleepers. Numerical, roller rig and natural experiments were carried out for each stage giving acceptable agreement between the results. Types and positions of sensors as well as the criteria are recommended to diagnose the derailment case in the moving train.